Serum levels of adiponectin and visfatin in patients with lichen planus: a case-controlled study - Sahar A Ismail; Ibrahim Mwafey; Sotohy A Mohamed (Wolters Kluwer Medknow Publications, 2017)
Background The association of adipokines with lichen planus (LP) is still obscure. Data regarding their effect on other immunological and inflammatory disorders suggest a probable role of adipokines in the pathophysiology of LP. Objective The objective of the study was to investigate serum levels of adiponectin and visfatin in patients with LP compared with healthy controls and to consider their relation to disease duration and obesity markers. Patients and methods A case-controlled study was conducted, which included 49 patients with LP and 40 healthy controls. Adiponectin and visfatin serum levels were measured using enzyme-linked immunosorbent assays. Results Patients with LP showed lower serum levels of adiponectin than healthy controls, with significant inverse correlation with disease duration, BMI, and waist circumference. Cutaneous and mucocutaneous LP showed lower serum levels of adiponectin than oral LP. Visfatin serum level was higher in patients with LP compared with healthy controls, with significant positive correlation with BMI and waist circumference. Conclusion Our data suggested that adiponectin and visfatin act together through modulation of the inflammatory setting of patients with LP. Because of the significant correlations of adiponectin and visfatin with obesity markers, the physical complications of obesity should be emphasized to patients with LP.